International Trade Unionism: The United Mine Workers in Eastern Canada, 1900-1920 - Williams, Brian (Relations industrielles / Industrial Relations, 1986)
This paper reports evidence gathered in the case ofthe United Mine Workers of America and its activities in Eastern Canada during the period 1900-1920.